Korzenie albo słodko-gorzkie przyprawy „nowego regionalizmu” - Szkaradnik, Katarzyna (Śląskie Studia Polonistyczne, 2014)
The review is an evaluation of a post-conference tome Nowy regionalizm w badaniach literackich. Badawczy rekonesans i zarys perspektyw, edited by Małgorzata Mikołajczak and Elżbieta Rybicka. The author focuses on theoretical propositions included in the book, situating them in the context of a topographical shift and a revival of interest in regional literature, which cannot be reduced to notions of “small homeland” or “spice literature”. She discusses strategies and interpretations presented in the articles, chiefly devoted to literature on cross-border areas: Western Lands, Podlasie, and Upper Silesia. In the review, the author agrees with the point on the importance of discovering non-canonical literature and the potential of critical “peripheral” writing, but doubts are also expressed, since the status of the new regionalism is in itself problematic.